Modeling HIV-1 intracellular replication : two simulation approaches - Zarrabi, Narges. (2013)
Many mathematical and computational models have been developed to investigate the complexity of HIV dynamics, immune response and drug therapy. However, there are not many models which consider the dynamics of virus intracellular replication at a single level. We propose a model of HIV intracellular replication where infected cells undergo a single cycle of virus replication. A cell is modeled as an individual entity with certain states and properties. The model is stochastic and keeps track of the main viral proteins and genetic materials inside the cell. Two simulation approaches are used for implementing the model: rate-based and diffusion-based approaches. The results of the simulation are discussed based on the number of integrated viral cDNA and the number of viral mRNA transcribed after a single round of replication. The model is validated by comparing simulation results with available experimental data. Simulation results give insights about the details of HIV replication dynamics inside the cell at the protein level. Therefore the model can be used for future studies of HIV intracellular replication in vivo and drug treatment.